2007
DOI: 10.1111/j.1365-2443.2007.01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Host factor Ebp1: Selective inhibitor of influenza virus transcriptase

Abstract: Influenza virus RNA polymerase is composed of three virus-coded proteins, and is involved in both transcription and replication of the negative-strand genome RNA. Subunit PB1 plays key roles in both the RNA polymerase assembly and the catalytic function of RNA polymerization. Using yeast two-hybrid screening, a HeLa cell protein with the molecular mass of 45 kDa was identified. After cloning and sequencing, this protein was identified to be Ebp1, ErbB3-binding protein. Epb1 specifically interacts with PB1 both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Although they found that Hsp90 interacted with the PB2 subunit through both the N-terminal chaperone domain and the middle region, the virus RNA synthesis stimulatory activity of Hsp90 was only dependent on an acidic domain of the middle region (23). In addition, a host factor, Ebp1, was reported to interact with the catalytic region of PB1 subunit and thus interfere with in vitro RNA synthesis activity of influenza virus RNA polymerase (3P complex) (53). Therefore, our findings in this study further extend our knowledge on host factors that are specifically involved in stimulating viral RNA polymerase activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although they found that Hsp90 interacted with the PB2 subunit through both the N-terminal chaperone domain and the middle region, the virus RNA synthesis stimulatory activity of Hsp90 was only dependent on an acidic domain of the middle region (23). In addition, a host factor, Ebp1, was reported to interact with the catalytic region of PB1 subunit and thus interfere with in vitro RNA synthesis activity of influenza virus RNA polymerase (3P complex) (53). Therefore, our findings in this study further extend our knowledge on host factors that are specifically involved in stimulating viral RNA polymerase activities.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, from a recent genomic screening, only two factors that negatively modulate viral polymerase activity were found (75), and, furthermore, the physiological role of only a very few cases of influenza virus repressors has been characterized. Standing out among these are the characterization of Ebp-1, a suppressor of the androgenmediated transcription that inhibits RNA synthesis of the viral polymerase in vitro (76); cyclophilin E, which negatively regulates virus life cycle in infected cells (77); annexin 6, which impairs virus budding (78); and the HAX1 protein, which impedes the nuclear translocation of the PA polymerase subunit (79).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 was shown to interact with PB2 and enhance influenza viral RNA synthesis (35). Ebp1 (ErbB3-binding protein) was identified as a PB1 interactor and found to selectively interfere with in vitro RNA synthesis by influenza virus RNA polymerase (17). For these given examples, there has been no evidence that the interactions vary between species or could account for host range restrictions.…”
Section: Discussionmentioning
confidence: 99%